PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019–2024 - Alia Febrianti; Wirawan Widjanarko; Franciscus Dwikotjo Sri Sumantyo (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to examine and analyze the influence of liquidity (Current Ratio/CR), leverage (Debt to Equity Ratio/DER), and profitability (Return on Assets/ROA) on stock prices—both partially and simultaneously—among consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2024. A quantitative method with a panel data regression approach was applied to 60 observations (10 companies × 6 years) selected through purposive sampling and processed using EViews. Model selection tests identified the Random Effect Model (REM) as the most appropriate estimator. The results show that liquidity and profitability have no significant effect on stock prices, while leverage has a significant negative effect. Simultaneously, the three variables significantly affect stock prices, explaining 35.40% of the variance (R²). Future research is recommended to incorporate additional fundamental indicators such as EPS, PBV, and ROE, as well as macroeconomic variables such as inflation, interest rates, and exchange rates.